Genotyping of Indian antigenic, vaccine, and field Brucella spp. using multilocus sequence typing - Shome, Rajeswari; Krithiga, Natesan; Shankaranarayana, Padmashree B; Jegadesan, Sankarasubramanian; Udayakumar S, Vishnu; Shome, Bibek Ranjan; Saikia, Girin Kumar; Sharma, Narendra Kumar; Chauhan, Harshad; Chandel, Bharat Singh; Jeyaprakash, Rajendhran; Rahman, Habibur (The Journal of Infection in Developing Countries, 2016)
Introduction: Brucellosis is one of the most important zoonotic diseases that affects multiple livestock species and causes great economic losses. The highly conserved genomes of Brucella, with > 90% homology among species, makes it important to study the genetic diversity circulating in the country. Methodology: A total of 26 Brucella spp. (4 reference strains and 22 field isolates) and 1 B. melitensis draft genome sequence from India (B. melitensis Bm IND1) were included for sequence typing. The field isolates were identified by biochemical tests and confirmed by both conventional and quantitative polymerase chain reaction (qPCR) targeting bcsp 31Brucella genus-specific marker. Brucella speciation and biotyping was done by Bruce ladder, probe qPCR, and AMOS PCRs, respectively, and genotyping was done by multilocus sequence typing (MLST). Results: The MLST typing of 27 Brucella spp. revealed five distinct sequence types (STs); the B. abortus S99 reference strain and 21 B. abortus field isolates belonged to ST1. On the other hand, the vaccine strain B. abortus S19 was genotyped as ST5. Similarly, B. melitensis 16M reference strain and one B. melitensis field isolate were grouped into ST7. Another B. melitensis field isolate belonged to ST8 (draft genome sequence from India), and only B. suis 1330 reference strain was found to be ST14. Conclusion: The sequences revealed genetic similarity of the Indian strains to the global reference and field strains. The study highlights the usefulness of MLST for typing of field isolates and validation of reference strains used for diagnosis and vaccination against brucellosis.